Usulan Tata Zonasi dan Pola Sirkulasi Pengunjung di Area Sekitar Candi Singasari, Kabupaten Malang, Jawa Timur - Premana, I Kadek Riko; Suryada, I Gusti Agung Bagus; Titisari, Ema Yunita; Paramadhyaksa, I Nyoman Widya (Jurnal Arsitektur Universitas Udayana, 2025)
Singasari Temple, located in Malang Regency, East Java, is an important historical site from the 13th century that serves as a spiritual and architectural symbol of the Singasari Kingdom and an integral part of Javanese cultural identity. The increasing number of visitors and the development of tourism in the area pose challenges in the preservation of the temple and the management of its surrounding environment. Unmanaged tourism activities can threaten the physical integrity of the temple and reduce the quality of the visitor experience. To address these issues, a proposed zoning and visitor circulation pattern was developed. The zoning includes a core zone with limited access, a buffer zone to protect from the impact of activities, and a support zone for facilities such as an information center and parking area. The circulation pattern is arranged to manage tourist movement, avoid congestion in sensitive areas, and improve comfort. Quantitative methods were used to assess the effectiveness of the proposal, including visitor data analysis and circulation simulations. The results showed that this strategy was effective in reducing visitor congestion, increasing satisfaction, and reducing the risk of damage to the temple. With the implementation of this strategy, Singasari Temple can be maintained as a valuable historical site and a sustainable tourism destination, ensuring its authenticity and historical value are maintained. Keywords: Singasari temple, historical site, zoning, visitor circulation pattern